Analisis Strategi Pemasaran Bank Syariah Berbasis Digital Fintech (Financial Technology) Terhadap Pelayanan Nasabah : (Studi Kasus Pada PT. Bank Muamalat KCU Medan Baru) - Chairunnisa Dian Puspa; Muhammad Lathief Ilhamy Nasution (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Digital financial services provided by fintech companies operate or make use of digital technologies. One of the banks that has offered digital fintech-based services are Bank Muamalat KCP Medan Baru. These services include virtual account services, cash management systems, online banking, m-banking (M-DIN), and ATMs. the necessity of putting into practice marketing tactics that increase client happiness and faith in these services. The purpose of this study is to identify the Bank Muamalat KCP Medan Baru's digital fintech-based marketing strategy for customer service. At Bank Muamalat KCP Medan Baru, this kind of research is considered field research. This study is descriptive qualitative in nature. Interviews and documentation were used to obtain data. The key data sources used were interviews with Bank Muamalat sub-branch managers, customer care representatives, and consumers KCP Medan Baru, whereas secondary sources are drawn from written works or other types of documentation to supplement primary data. According to the research, it is known that Bank Muamalat KCP Medan Baru has applied a number of shari'ah marketing indicators, including a number of marketing mix components. Promotion has dominated marketing tactics throughout the Bank's existence. Brands, services, and procedures produce marketing value. Additionally, Bank Muamalat KCP Medan Baru is inextricably linked to the three key tenets of shari'ah marketing—piety, moderation, and virtue. The Principle of Piety is the one that is used the most frequently. Additionally, Bank Muamalat KCP Medan Baru should assess or enhance its marketing tactics for digital fintech services continuous attempts to increase usage of the system due to the fact that some clients are still unaware of Muamalat's digital fintech offerings, particularly its virtual accounts, cash management systems, and online banking.